PENINGKATAN MUTU PENDIDIKAN MELALUI EVALUASI KINERJA GURU DALAM SOCIETY 5.0 - Huda Sholeh (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Teacher Performance Evaluation aims to improve the quality of education for students by helping teachers realize their potential and carry out their duties as effectively as possible. Teacher performance evaluation focuses on performance and efforts to improve work performance. All teachers must have clear job descriptions because they play an important role in achieving student success. This research uses library research methods. This research method is based on literature findings or library references. Data is collected from various sources: reading, storing, analyzing, and categorizing data to draw reliable conclusions. The results of teacher performance evaluations can be the basis for making corrections, guiding and developing, and providing achievement scores and scores related to teacher career development by regulations. Applicable. If all this can be done well and objectively, high-quality and competitive training can be implemented immediately so that we can build a dignified nation. This makes it possible for teachers with high performance and commitment to be able to plan, implement, and evaluate learning effectively, efficiently, and responsibly. It can be concluded that teacher performance evaluations, which are evaluated based on scientific abilities, behavioral skills, work quality, personal abilities, and communication skills that can create and describe teacher performance activities, can provide quality services for students and the community.